Pengaruh Motivasi, Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Guru Sd Yos Sudarso Batam Center - Sanga, Laurensius Dihe; Dabur, Feliks (Tractare: Jurnal Ekonomi-Manajemen, 2023)
This study aims to determine the effect of motivation, workload, and work environment on teacher performance at SD Yos Sudarso Batam Center. This research method uses quantitative research techniques. The sample method in this study used saturated sampling, so the number of samples used was 49 respondents. The data collection technique used in this research is literature study and distributing questionnaires. The results of the study with a significance level of 5% indicate that: (1) Motivation variable has a positive and significant effect on teacher performance, this can be seen from the significance value of 0.581 > 0.05 and the tcount of 2.555 > ttable 1.677. (2) Workload variable has a positive and significant effect on teacher performance, this can be seen from the significance value of 0.144 > 0.05 and the value of tcount 2.486 > ttable 1.677. (3) The work environment variable has a positive and significant effect on teacher performance, this can be seen from the significance value of 0.903 > 0.05 and the value of tcount 2,223 > ttable 1,677. (4) Motivation, Workload and Work Environment Variables togethera positive and significant effect on Teacher Performance, this can be seen from the value of Fcount 3.348 > Ftable 2.790 with significance value 0.127.